THE RELATIONSHIP BETWEEN SPIRITUAL INTELLIGENCE AND THE PERFORMANCE OF XYZ BANK EMPLOYEES - Galuh Aditya Ningtyas; Niselia Niselia; Indriwati Gunawan (International Journal Labs, 2022)
Every company expects its employees to work satisfactorily following predetermined targets. This is expected to have an impact on the progress of the company to be able to compete with other companies. An employee who has good performance results is expected to have high spiritual intelligence, whose quality of life is based on values and a reluctance to cause unnecessary loss. This research aims to determine the relationship between spiritual intelligence and employee performance. The subject for this research were 150 employees of XYZ Bank, which was the result of sampling from the simple random sampling method. This research implemented a quantitative approach with the type of correlational research that used a survey method with a questionnaire. This research implemented Spiritual Intelligence Scale in the form of the Spiritual Intelligence Self Report Inventory (SISRI), which was adapted from King (? = 0.876), and the Employee Performance scale which referred to the perception of the Bank's employees XYZ (? = 0.829). Data analysis was performed using the Kolmogorov-Smirnov normality test with p = 0.157 (Sig.p > 0,05 or 5%) for spiritual intelligence variables and employee performance variables were not normally distributed because p = 0,014 (Sig.p > 0,05 or 5%). The correlation test was carried out using Spearman correlation analysis with p = 0.708 (Sig.p > 0,05 or 5%). Hence, it was found that there is no relationship between spiritual intelligence and the performance of XYZ Bank employees.